Cocaine addiction severity exacerbates the negative association of lifetime lead exposure with blood pressure levels: Evidence from a pilot study - Elena Colicino; Danielle B Hazeltine; Kelly M Schneider; Anna Zilverstand; Keren Bachi; Nelly Alia-Klein; Rita Z Goldstein; Andy C Todd; Megan K Horton (Wolters Kluwer Medknow Publications, 2019)
Background: High blood pressure (BP) is associated independently with cocaine use and lead exposure. It is not known whether cocaine use and lead exposure act jointly to disrupt cardiovascular health. Objective: To determine whether cocaine use modifies the association between cumulative lead levels and elevated BP. Materials and Methods: We measured cumulative tibia lead levels in 35 adults: 20 with cocaine use disorder (CUD) and 15 non-CUD controls using in vivo K-shell X-ray fluorescence. Generalized estimating equation regression determined associations between log2-transformed lead and BP (systolic, diastolic, and mean arterial pressure) and assessed the modifying association of cocaine use (as addiction severity) on the lead-BP relationship, adjusting for age, sex, smoking, and education. Sensitivity analyses included correction for potential selection bias. Results: Cases and controls differed by sex (%male: 90% vs. 67%), age (50.7 vs. 39.9 years), education (12.8 vs. 14.4 years), and tibia lead (3.50 vs. 2.35 μg/g). Lead was positively associated with systolic (P = 0.01) and diastolic BP (P = 0.01). We observed an interaction between lead and addiction severity on BP (P values for systolic BP: 0.01, diastolic BP: 0.003, and mean arterial BP: <0.0001); the association was stronger among individuals with more severe cocaine addiction: Systolic BP: Est.: 17.89, 95% confidence interval (CI): 9.52; 26.26, diastolic BP Est.: 17.89, 95% CI: 7.33; 13.79, mean arterial BP: Est.: 13.09, 95% CI: 10.34; 15.83. Conclusions: Lead was adversely associated with BP. This association was strongest among individuals with more severe cocaine addiction. The results from this small pilot study suggest that the interaction between lead and cocaine should be considered in studies of substance abuse-related health outcomes.